IMPLEMENTASI PERAN FORUM KEMITRAAN POLISI MASYARAKAT DALAM MENCEGAH KEJAHATAN DI WILAYAH HUKUM POLSEK MARO SEBO - M. Rudi Hartono (Jurnal Ilmiah Universitas Batanghari Jambi, 2016)
The activities of the Police Department that deals with the processes in the society demands the existence of a partnership between the police and the community in preventing crime. The police should be able to put itself in tune with the expectations of the community so that the community can be involved actively in crime prevention. One of the strategies of prevention against threats and disruption of security and public order can be done by the police with the utilization of the ability of citizens, selective, efficient and effective in detecting the possibility of evil. The community is a party to the most understanding of the problem of evil and ketidaktertiban that occur in the environment. To prevent crime the police should conduct a consultation (consultation) with the community to be able to adjust the service/police action (adaptation) according to needs, mobilize (mobilization) potential that exists within the community so that the retrieved a method of solving the problem (problem solving) or solution based on the issue in accordance with the point of view of the citizens. Especially in jurisdictions Polsek Maro Sebo, in 2014, there is a wide variety of forms of crimes that occurred as robbery, theft of livestock theft, empty House, penodongan, gambling and so on. This gives rise to anxiety and inconvenience for the people who live in the districts of Maro Sebo. Information about ketidaktertiban most accurate when received from the community. The community will inform the ketidaktertiban problem when the community is easy to report it, the community knows the benefits if the reported problem ketidaktertiban, and people are sure the police can handle the matter completely. Useful information will come from the local people when the police have built a relationship based on trust with the communities they serve. Therefore required a new partnership between the police and the community.Keyword  : Police, Partnerships, Society, Crime